Performance enhancement criteria in the pharmaceutical industry of Bangladesh: a qualitative study - Siddique, Mohammad Masud; Wan Husain, Wan Rohaida; Islam, Rafikul (2025)
The purpose of this study is to identify and explore key criteria and sub-criteria essential to assess the operational performance of pharmaceutical companies in Bangladesh. By focusing on critical aspects of business operations and management, the research seeks to provide a robust foundation for evaluating and enhancing performance in the pharmaceutical sector. The study employs a qualitative methodology, combining an extensive literature review with insights from 15 expert interviews. A purposive judgmental sampling technique was used to select participants. The respondents were top- and mid-level executives, policymakers, and quality assurance managers. Data analysis was conducted using NVivo software to identify and structure the criteria and sub-criteria. The study identified eight key criteria and 26 sub-criteria to develop the hierarchical performance assessment model. These include leadership, strategic planning, operations management, human resource management, customer focus, quality assurance, communication, and business results. The study's findings are based on qualitative data from expert interviews and literature reviews, which may not fully capture all perspectives (e.g., frontline employees, regulatory bodies, policymakers, and others) within the pharmaceutical sector. Future studies may employ quantitative methodology such as Analytic Hierarchy Process (AHP) method to prioritise the identified criteria and sub-criteria and develop a business excellence model. This study represents a pioneering effort to develop a comprehensive performance assessment framework specific to the pharmaceutical industry in Bangladesh by identifying industry-relevant performance measuring criteria and sub-criteria